The Influence of Managerial Ownership and Company Growth on Company Value through Institutional Ownership as a Moderation Variable - Agam Mei Yudha; Yamasitha Yamasitha; Yosi Yulia; Putri Intan Permata Sari (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This study aims to find out how much the discussion of Company Value through Institutional Ownership as a moderation variable: Managerial Ownership and Company Growth (In Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2016-2020). Data collection methods through ICMD and IDX sites and literature studies. The method of analysis used is regression analysis.The results of this study were obtained: (1) Managerial Ownership partially affects the Value of the Company (2) Company Growth partially has a significant effect on the Company Value (3) Managerial Ownership and Company Growth partially affects the Value of the Company (4) Managerial Ownership partially affects the Value of the Company with institutional ownership as a moderation variable (5)  The Company's growth partially has no significant effect on the Value of the Company with institutional ownership as a moderation variable (6) Managerial Ownership and Company Growth partially affect the Value of the Company with institutional ownership as a moderation variable.